The role of mitochondrial survivin in phospholipid biosynthesis - Dunajova, Lucia (2016)
Survivin is an essential protein that is highly overexpressed in most human cancers and is known to be involved in many cellular processes by virtue of its different locations and interacting partners in the cell. At mitosis it is part of the chromosomal passenger complex, which ensures correct temporal and spatial regulation of chromosome movements and cytokinesis. Survivin also acts in apoptosis suppression via distinct mechanisms many of which have been ascribed to the mitochondrial pool of survivin. However, it is still unclear precisely how survivin gains access to this organelle, its other possible functions while there and its effect on mitochondrial morphology. Though mitochondria play an essential role in apoptosis induction and execution, they also provide phospholipids for incorporation into membranes. Of particular interest to this study, they synthesise phosphatidylethanolamine (PE), by decarboxylation of phosphatidylserine, which is catalysed by phosphatidylserine decarboxylase (PSD). The purpose of this thesis was to test the hypothesis that mitochondrial survivin regulates PSD-mediated conversion of PS to PE in the mitochondria. This thesis shows PSD is a novel partner of survivin which interacts with it both in vivo and in vitro. The interaction was mapped to the N-terminal BIR domain of survivin. Furthermore, only mature catalytically active PSD could interact with survivin, suggesting that survivin regulates PSD activity, and thereby could regulate PE availability to the cell. In addition to discovering that survivin is a novel regulator of PSD activity, this thesis also identified a second isoform of human PSD, and discovered that the NH2 terminal ten amino acids of survivin area non-canonical mitochondrial targeting sequence. As PE is an essential phospholipid which is required for maintenance of mitochondrial integrity, successful cytokinesis and lipidation of autophagosomes during autophagy, the identification of mitochondrial survivin as a regulator of PSD activity can be expected to have a significant impact on cellular health. Therefore, this thesis identified a completely novel mechanism by which mitochondrial survivin could be further fuelling tumorigenesis in vivo.